NN -> NN pi(+) reaction near threshold in a chiral power counting approach - Rocha, Carlos A. da [UNESP]; Miller, Gerald A.; Van Kolck, Ubirajara (American Physical Soc, 2000)
Power-counting arguments are used to organize the interactions contributing to the NN-->d pi,pn pi reactions near threshold. We estimate the contributions from the three formally leading mechanisms: the Weinberg-Tomozawa (WT) term, the impulse term, and the Delta-excitation mechanism. Subleading but potentially large mechanisms, including S-wave pion rescattering, the Galilean correction to the WT term, and short-ranged contributions are also examined. The WT term is shown to be numerically the largest, and the other contributions are found to approximately cancel. Similarly to the reaction pp-->pp pi(0), the computed cross sections are considerably smaller than the data. We discuss possible origins of this discrepancy.